2022
DOI: 10.1177/15533506221123355
|View full text |Cite
|
Sign up to set email alerts
|

USE of Biodegradable STENTS in Pancreaticoduodenectomy: Initial Experience

Abstract: Background. Plastic stents have been used to avoid postoperative pancreatic fistula (POPF) following Whipple’s Pancreaticoduodenectomy (WPD), but they may cause some stent-related complications. Biodegradable stents have been recently introduced and might be a safe alternative. Here we present our initial experience with their use. Methods. Between March 1, 2020, and September 30, 2020, ten (10) consecutive patients underwent WPD. They all had conventional two-layer pancreaticojejunostomy with the placement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Anastomosis was then completed using anterior row sutures. A similar use of an uncovered coronary artery stent with positioning under X-ray guidance was recently reported by Huscher et al [26], and the use of biodegradable stents in 10 patients was reported by Sulieman et al [27]. Although the use of expandable internal PJA stents is still in its infancy, the initial results of their use are promising in terms of reducing the clinically relevant POPF rate and major morbidity with no stent-related complications [26, 27].…”
Section: Transanastomotic Internal Pancreatic Duct Stentsupporting
confidence: 59%
“…Anastomosis was then completed using anterior row sutures. A similar use of an uncovered coronary artery stent with positioning under X-ray guidance was recently reported by Huscher et al [26], and the use of biodegradable stents in 10 patients was reported by Sulieman et al [27]. Although the use of expandable internal PJA stents is still in its infancy, the initial results of their use are promising in terms of reducing the clinically relevant POPF rate and major morbidity with no stent-related complications [26, 27].…”
Section: Transanastomotic Internal Pancreatic Duct Stentsupporting
confidence: 59%